1998
DOI: 10.1002/jlb.63.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione peroxidase activity and mRNA expression in eosinophils and neutrophils of asthmatic and non-asthmatic subjects

Abstract: Asthma has been reported to be associated with a reduction in the activity of glutathione peroxidase (GSH-Px), an important antioxidant enzyme. However, the expression of GSH-Px enzyme activity has not previously been investigated in human eosinophils, which are important inflammatory cells involved in asthma. Reverse transcriptasepolymerase chain reaction and Southern blotting demonstrated that eosinophils express GSH-Px mRNA and the relative expression of GSH-Px was greater in eosinophils than in neutrophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…In contrast, PMN expressed mainly monomer and trimer isomers, rather than dimer and tetramer isomers, of GSH-Px. These results are compatible with those of Misso et al [30], who showed that normal neutrophils contain mainly monomer and trimer isoforms of GSH-Px. Because the GSH-Px enzymatic activity of T lymphocytes is much higher than that of PMN, we speculated that the dimer and tetramer isoforms of GSH-Px may possess more potent antioxidant activity than the monomer and trimer isoforms.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, PMN expressed mainly monomer and trimer isomers, rather than dimer and tetramer isomers, of GSH-Px. These results are compatible with those of Misso et al [30], who showed that normal neutrophils contain mainly monomer and trimer isoforms of GSH-Px. Because the GSH-Px enzymatic activity of T lymphocytes is much higher than that of PMN, we speculated that the dimer and tetramer isoforms of GSH-Px may possess more potent antioxidant activity than the monomer and trimer isoforms.…”
Section: Resultssupporting
confidence: 93%
“…In addition, compared to normal cells, SLE-T and SLE-PMN tend to have decreased ATP production (Figure 1(d)). This decreased ATP production reflects mitochondrial functions impaired by activation-induced cell death [36, 37] and decreased redox capacity in SLE [2, 4, 30]. Abnormal glucose bioenergetics in SLE cells owing to defective expression of GLUT-3 and GLUT-6 on the cell surface can lead to impaired immune functions in active SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils were isolated by centrifugation of whole blood on Percoll (density 1.088, GE Healthcare Bio-Sciences, Sydney, Australia), followed by hypotonic lysis of erythrocytes and immunomagnetic selection of neutrophils using CD16 microbeads (MACS, Miltenyi Biotec, Sydney, Australia), as previously described [17].…”
Section: Isolation Of Neutrophils From Peripheral Bloodmentioning
confidence: 99%
“…It is also possible that increased GPX activity might relate to over-expression of the GPX gene. Misso et al 39 showed increased expression of GPX mRNA in eosinophils from AIA patients. Comhair et al 40 reported an eight-fold increase in GPX mRNA in bronchial epithelial cells after exposure to reactive-oxygen species and glutathione, a cofactor for GPX.…”
Section: Discussionmentioning
confidence: 97%